PENERAPAN COOPERATIVE LEARNING MODEL THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN EKONOMI DI KELAS XI IPS 3 SMA NEGERI 1 KAUMAN - pijar, HARTATIK (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2015)
ABSTRACT: Human being has different things on the potent, historic, background, and future hope. Becauseof the differences, human being can take and give This research is to express the problem: The purpose of this research is to: This research used classroom action research for 3 cycles. Every cycle is formed into 4 stages:Planing, Activity and Observation, Reflexion and Revision. This research is aimed to the students of XI IPS 3.The data taken in the form of formative test result and observation sheet the teaching-learning process.From the data analysis, we know that the student’s achievement become rising from Cycle I – CycleIII, that is: Cycle I The research result is the cooperative learning method by using Think-Pair-Share model can givepositive effect towards the motivation and the student’s achievement of XI IPS, SMAN 1 Kauman. This modelof learning is also to be used as one of alternative method to study “Ekonomi”.Keywords: Learning Achievement, Cooperative Learning, Think-Pair-Share model